Aktuálne postupy u pacientov so zlomeninami proximálneho femuru užívajúcich protidoštičkovú a antikoagulačnú liečbu - Šteňo, B; Bátorová, A; Jankovičová, D; Prigancová, T; Hložník, J; Švec, A; Chandoga, I (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
Proximal femur fractures (PFF) pose a major challenge in elderly patients with severe comorbidities and receiving antithrombotic therapy since according to the latest guidelines the surgery should be performed as soon as possible, preferably within 24 hours, to reduce mortality and morbidity. This review outlines the practical approach to surgical management of PFF that relies on increasing evidence of safety of early surgery in patients with PFF receiving antiplatelet and anticoagulant therapy. We have also used information from the existing evidence-based guidelines for elective/planned surgery in patients with antithrombotic therapy. The practical approach can be summarised as follows: • Antiplatelet therapy - discontinuation of acetylsalicylic acid (ASA) and clopidogrel in monotherapy or in combination is not necessary prior to surgery. In case of bleeding, antifibrinolytic therapy is recommended as well as administration of platelet concentrate which is rarely needed. • In patients taking warfarin, reversal of its effects is recommended by early administration of vitamin K to allow surgery to be performed within 24 hours. Prothrombin complex concentrate (PCC) as a second-line drug is reserved for extreme cases only. Warfarin therapy is resumed 24 hours after surgery. • Direct oral anticoagulants must be discontinued 24-48 hours prior to surgery, possibly longer depending on the type of drug, time of administration of the last dose, and renal function. In extreme cases, an antidote (idarucizumab, off-label andexanet) can be administered prior to surgery, or PCC in case they are unavailable. Anticoagulation therapy is resumed in 24-48 hours. • Neuraxial anaesthesia is possible when ASA is taken by the patient and in case of effective warfarin reversal. • In early surgery and rapid restart of anticoagulant therapy, bridging therapy with LMWH is not indicated except for in cases with extreme risk of thrombosis. Key words: proximal femur fracture, antiplatelet therapy, anticoagulant therapy, perioperative management.
Keywords: Anticoagulants; Femoral Fractures; antikoagulancia; Warfarin; inhibitory agregace trombocytů; Humans; lidé; fraktury proximálního femuru; fraktury femuru; Platelet Aggregation Inhibitors; Proximal Femoral Fractures; Aspirin; warfarin